Comparative performance of three experimental hut designs for measuring malaria vector responses to insecticides in Tanzania. (December 2016) - Massue, Dennis; Kisinza, William; Malongo, Bernard; Mgaya, Charles; Bradley, John; Moore, Jason; Tenu, Filemoni; Moore, Sarah
Abstract Background Experimental huts are simplified, standardized representations of human habitations that provide model systems to evaluate insecticides used in indoor residual spray (IRS) and long-lasting insecticidal nets (LLINs) to kill disease vectors. Hut volume, construction materials and size of entry points impact mosquito entry and exposure to insecticides. The performance of three standard experimental hut designs was compared to evaluate insecticide used in LLINs. Methods Field studies were conducted at the World Health Organization Pesticide Evaluation Scheme (WHOPES) testing site in Muheza, Tanzania. Three East African huts, three West African huts, and three Ifakara huts were compared using Olyset® and Permanet 2.0® versus untreated nets as a control. Outcomes measured were mortality, induced exophily (exit rate), blood feeding inhibition and deterrence (entry rate). Data were analysed using linear mixed effect regression and Bland–Altman comparison of paired differences. Results A total of 613 mosquitoes were collected in 36 nights, of which 13.5 % wereAnopheles gambiae sensu lato, 21 %Anopheles funestus sensu stricto, 38 %Mansonia species and 28 %Culex species. Ifakara huts caught three times more mosquitoes than the East African and West African huts, while the West African huts caught significantly fewer mosquitoes than the other hut types. Mosquito densities were low, very little mosquito exit was measured in any of the huts with no measurable exophily caused by the use of either Olyset or Permanet. When the huts were directly compared, the West African huts measured greater exophily than other huts. As unholed nets were used in the experiments and few mosquitoes were captured, it was not possible to measure difference in feeding success either between treatments or hut types. In each of the hut types there was increased mortality when Permanet or Olyset were present inside the huts compared to the control, however this did not vary between the hut types. Conclusions Both East African and Ifakara huts performed in a similar way although Ifakara huts allowed more mosquitoes to enter, increasing data power. The work convincingly demonstrates that the East African huts and Ifakara huts collect substantially more mosquitoes than the West African huts.